2019
DOI: 10.1093/brain/awz174
|View full text |Cite
|
Sign up to set email alerts
|

CYP46A1 gene therapy deciphers the role of brain cholesterol metabolism in Huntington’s disease

Abstract: Dysfunctions in brain cholesterol homeostasis have been extensively related to brain disorders. The main pathway for brain cholesterol elimination is its hydroxylation into 24S-hydroxycholesterol by the cholesterol 24-hydrolase, CYP46A1. Increasing evidence suggests that CYP46A1 has a role in the pathogenesis and progression of neurodegenerative disorders, and that increasing its levels in the brain is neuroprotective. However, the mechanisms underlying this neuroprotection remain to be fully understood. Hunti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
103
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(111 citation statements)
references
References 84 publications
8
103
0
Order By: Relevance
“…We have previously shown that CYP46A1 expression was able to reduce the number and size of intranuclear protein aggregates within the striatum of HD mouse models and improve motor impairment [22], emphasizing the neuroprotective effect conferred by CYP46A1 in HD mice [22,24]. Here, we further show that CYP46A1 is able to decrease the number and size of HTT-MUT aggregates within a neuroblastoma cellular model of HD.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…We have previously shown that CYP46A1 expression was able to reduce the number and size of intranuclear protein aggregates within the striatum of HD mouse models and improve motor impairment [22], emphasizing the neuroprotective effect conferred by CYP46A1 in HD mice [22,24]. Here, we further show that CYP46A1 is able to decrease the number and size of HTT-MUT aggregates within a neuroblastoma cellular model of HD.…”
Section: Discussionsupporting
confidence: 64%
“…Impaired brain cholesterol metabolism has been broadly associated with neurodegenerative disorders. We and others showed that strategies aiming at restoring cholesterol metabolism using different strategies are beneficial in AD, SCA and HD mouse models [22,24,36,37]. Local synthesis/efflux of cholesterol is essential for the structural regulation of cells and membranes within the brain, being implicated in signal transduction, release of neurotransmitters and membrane trafficking [38].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CYP46A1 is crucial for brain cholesterol elimination, because it mediates cholesterol hydroxylation. Of note, a gene therapy approach with CYP46A1 has been recently tested in a mouse model of Huntington’s disease [ 119 ].…”
Section: Astrocyte-derived Molecules Affect Synaptic Plasticitymentioning
confidence: 99%